Science teaching with a CTS focus in the final years of elementary school: a literature review (2000-2021) (Research, Society and Development, 2022)
This study aimed to map articles published in the Portal of Periodicals of CAPES, from Nov./2000 to Mar./2021 on Science Teaching in the Early Years with a focus on Science, Technology and Society (STS). With a qualitative and quantitative approach, descriptive research and discursive textual analysis, whose descriptors were Science Teaching AND STS, Elementary School AND STS and Elementary School II AND STS, obtaining a total of 2,324 articles, of which only 35 were related to the topic; the Units of Meaning (UM) were chosen in view of the objectives described in each selected article, , where it was possible to group into three emerging categories: Teacher training, Textbook analysis, STS approach in Science teaching. Such categories made it possible to identify the most recurrent themes, the frequency of these publications, the methodology used by the authors, as well as the contribution in the field of Science teaching from the STS theme. It was found that in the STS approach, the first production took place in 2002; as for the type of methodology, action research and bibliographic research occur more frequently. Finally, it was noticed that the teaching of Science in the Initial Years with a STS focus is little used in the teaching and learning process in the country.